CONTACT-INDUCED CHANGE: THE CASE OF INDONESIAN - Udayana, I Nyoman (Lingual: Journal of Language and Culture, 2015)
This article aims at deeply explaining the languages influencing Indonesia. Indonesian stems from Malay. In its development, however, it is much influenced on the vernacular languages spoken in the Indonesian archipelago. It is shown that Indonesian has considerable influence from Javanese, ranging from lexicons to mosphosyntax. It is also shown that English as an international language inevitably influences Indonesian due to contacts